1995
DOI: 10.1287/orsc.6.1.93
|View full text |Cite
|
Sign up to set email alerts
|

The Research Design in Organization Studies: Problems and Prospects

Abstract: The paper is concerned with problems of research methodology in organization studies. It places the main emphasis on the “research design,” which is seen as an important tool for the planning, the substantiation and the practical guidance of research procedures. The explicit discussion and improvement of research designs is proposed to be a major contribution also to concept and theory development in Organization Science. The basic content of the paper is an empirical analysis and evaluation of the status quo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
0
14
0
7
Order By: Relevance
“…Unternehmen ist im internationalen Vergleich lange Zeit ein Spezifikum bundesdeutscher Organisationsforschung gewesen (Grunow 1995 Unternehmen ist im internationalen Vergleich lange Zeit ein Spezifikum bundesdeutscher Organisationsforschung gewesen (Grunow 1995 …”
Section: Durch Die Wissenschaft Generierte Organisationsdatenunclassified
“…Unternehmen ist im internationalen Vergleich lange Zeit ein Spezifikum bundesdeutscher Organisationsforschung gewesen (Grunow 1995 Unternehmen ist im internationalen Vergleich lange Zeit ein Spezifikum bundesdeutscher Organisationsforschung gewesen (Grunow 1995 …”
Section: Durch Die Wissenschaft Generierte Organisationsdatenunclassified
“…As a result, the organizational research has given rise to a multitude of qualitative case studies. The use of qualitative methods and the concentration on case studies has long been a distinctive feature of the German organizational research by international comparison (see Grunow 1995). Case studies do in fact have an important heuristic function in the research process, yet they entail some major problems: due to the small number of cases, they cannot provide any generalized statements; inter-subjective validation of the findings is impossible; and they can have only limited significance for social and economic research, which is more oriented towards explaining and predicting phenomena (see Hauptmanns and Rogalski 1992).…”
Section: Research Questionsmentioning
confidence: 99%
“…However, theory development and testing are often not done well in organizational research, a subset of which is research on organizational computing infrastructures (Merton 1967;Sutton and Staw 1995;Weick 1995). For example, Grunow (1995) reported on the methodological and theoretic approaches to 303 papers concerning organizational research. He found that 78% of these papers did not align theory to their research questions and 82% of the papers could not contribute meaningful results to theory development.…”
Section: The Role Of Theorymentioning
confidence: 99%